Peat stratigraphy mapping using ground penetrating radar and geotechnical engineering implications - Adepelumi, Adekunle; Akindulureni, John; Agih, Christian; Olubodun, Babakayode; Evinemi, Isaac (International Journal of Advanced Geosciences, 2014)
Ground Penetrating Radar (GPR) surveys was carried out in southwestern part of Lagos, Nigeria with a view of delineating the subsurface peat stratigraphy that would aid geotechnical engineering design of the appropriate soil stability processes . The GPR study was conducted along seven (7) parallel traverses trending E-W using the GSSI SIR-3000 200MHz monostatic shielded antenna. The mineralogy, micro-fabrics and morphology of the delineated stratigraphy was determined using the scanning electron microscope (SEM) and X-Ray diffraction (XRD) methods. The results obtained revealed the presence of five subsurface geological layers, distinct geomorphological features, and high, moderate and low amplitudes, to continuous and discontinuous planar radar facies structures. Borehole information confirms the occurrence of shallow peat and plastic clay layers beneath the area. SEM and XRD analyses of the field samples obtained showed the dominance of kaolinite, illite and quartz minerals in the clay/peat mapped. The derived engineering parameters suggest that the peats found in the area are fibrous peat with low strength and medium to low bedding stress. It is observed that the peat generally depict high compressibility value and low shear modulus. Our findings confirm the efficacy and relevance of GPR technique for pre-construction engineering investigations. Keywords: Compressibility, GPR, Mineralogy, Peat Stratigraphy, Soil Stability.